Factors Influencing Destination Loyalty for Ratchaburi province, Thailand: Proposed Strategic Operations for Cultural Tourism Development - Itthiophakorn, Dhouchatorn; Preudhikulpradab, Sirichai (Dusit Thani College Journal, 2024)
Ratchaburi, a central province of Thailand, is a standout in terms of diverse ethnicity, cultures, and other tourism potential, but they are inadequately receiving higher awareness, and/or adequate attention and understanding of its cultural and ethnic diversity from local communities, and domestic tourists in a realm of cultural tourism. Hence, the researcher aimed to understand the factors and gradually propose tourism strategic implementations to leverage its cultural tourism potential. There are two objectives for this quantitative study, which are 1) to study factors influencing destination image and memorable tourism experiences on destination loyalty towards Ratchaburi province in cultural tourism, and 2) to examine the current situation of factors influencing destination loyalty from the perspective of Ratchaburi’s cultural tourism development. The target population was Thai people who have experience traveling to the cultural-related tourism destinations in Ratchaburi by using the multi-stage sampling method. The researcher used 325 structured questionnaires for data collection, and later deployed the Simple Linear Regression (SLR) and Multiple Linear Regression (MLR) to statistically analyze the data. The findings revealed that the factors that significantly influenced Ratchaburi's destination loyalty in terms of cultural tourism were authentic experience, meaningfulness, local culture, destination image, memorable tourism experience, and involvement. Unfortunately, knowledge was the least significant factor for cultural tourism in the province. The researcher concluded by proposing a set of recommendations for the strategic implementation of cultural tourism development. The recommended implications are 1) open access to cultural knowledge, 2) creative tourism initiatives, and 3) innovative and smart adaptation. These implications were critically vital to leverage engagement and understanding of local cultures and ethnicity living in different parts of the province to sustainably develop cultural tourism.